LOCAL BUSINESS DYNAMICS IN THE ERA OF GLOBALISATION: LEGAL UNCERTAINTY, GLOBAL COMPETITION, AND ADAPTIVE STRATEGIES OF LOCAL ENTREPRENEURS - Gunawan Widjaja; Dyah Ersita Yustanti; Rio Johan Putra (CV. Adiba Aisha Amira, 2025)
This study examines the dynamics of local businesses in the era of globalisation, focusing on the challenges of legal uncertainty, global competition, and the adaptive strategies implemented by local entrepreneurs. Globalisation has opened up opportunities for market access, but it has also increased the risks to the sustainability of local businesses due to the entry of global players who are superior in terms of capital, technology, and networks. Legal uncertainty manifests in various forms, including inconsistent regulatory changes, incompatibility with international law, and weak protection for domestic businesses. Through a literature review, this study identifies that local entrepreneurs address these challenges through product innovation, digital transformation, human resource development, and business network expansion. These adaptive strategies are not only important for maintaining their position in the domestic market but also key to penetrating global markets. Government support in the form of clear regulations, access to technology, and fair legal protection is essential for local businesses to develop sustainably. This study provides insights for business actors, government, and academics to understand the real conditions of local businesses in facing the ever-changing global era.